HUBUNGAN MOTIVASI PASIEN TUBERCULOSIS PARU TERHADAP KEPATUHAN DALAM MINUM OBAT - Fiqri " Abdullah; Siti " Rahmalia; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Pulmonary tuberculosis is an infectious disease caused by mycobacterium tuberculosis bacteria that can infect lung organ. The aim of research is to determine the correlation between motivation pulmonary tuberculosis patient with adherence on medication in Lung respiratory pulmonary discipline clinic at Arifin Achmad Hospital province of Riau. The design of this research a descriptive correlation with cross sectional approach. The total samples is 66 respondents was taken by purposive sampling technique. Data was collection by questionnaires had been test validity motivation ( r = 0,445 – 0,699) with reliability motivation (0,886) and test validity adherence (r = 0,550 – 0,703) with reliability adherence (0,792). Data collection was analysed by univariate & bivariate used distribution frequention and chi square. The results of research showed that 39 respondents with high motivation (59,1%) and 41 obedient respondents (62,1%). The results of study showed that there is significantly the correlation between motivation pulmonary tuberculosis patient with adherence on medication. According the result of research it’s mean the tb patient who adherence on medication will be high risk be come tb permanent will develop multi drug resistence. Keyword: Adherence, Motivation, Pulmonary Tuberculosis